Strengthening Social Capital in Motor Vehicle Tax Services: Developing a Regional Tax Governance Model in West Java Province - Mohamad Deni Zakaria; Nurliah Nurdin; Marja Sinurat; Tjahjo Suprajogo (Department of Public Administration, 2026)
Motor Vehicle Tax (MVT) is one of the principal sources of Regional Original Revenue (PAD) in West Java Province. Although MVT revenue has continued to increase, persistently high tax arrears indicate that improvements in public services and digital transformation alone have not been sufficient to foster sustainable voluntary taxpayer compliance. This study aims to examine the implementation of social capital in Motor Vehicle Tax services in West Java Province based on Robert D. Putnam’s dimensions of network, trust, and norms, and to develop a social capital-based model for strengthening regional tax governance. A qualitative case study approach was employed. Data were collected through in-depth interviews with 25 participants representing the Regional Revenue Agency (Bapenda), Samsat officers, the Indonesian National Police, PT Jasa Raharja, and taxpayers across five Samsat offices, complemented by observations and document analysis. The findings indicate that the network dimension is manifested through collaboration among Bapenda, the Indonesian National Police, PT Jasa Raharja, banking institutions, and digital payment platforms, which expands service accessibility and administrative efficiency. The trust dimension has been strengthened through service transparency, digital transformation, and simplified administrative procedures, although these improvements have not yet fully translated into voluntary taxpayer compliance. Meanwhile, the norms dimension remains relatively weak because taxpayer behavior continues to be influenced more by sanctions and policy incentives than by collective civic awareness. Based on these findings, this study proposes a Social Capital-Based Motor Vehicle Tax Service Model, which conceptually explains how the interaction of network, trust, and norms may strengthen voluntary taxpayer compliance and contribute to more effective regional tax governance.